Answer:
The general rule for the nth term of this sequence will be:
![a_n=3na+9a](https://img.qammunity.org/2021/formulas/mathematics/college/k9n9gy6quugesn4o83d3ws45gsvlp0sltt.png)
Explanation:
Given the sequence
12a, 15a, 18a, 21a, 24a,...
An arithmetic sequence has a constant difference 'd' and is defined by
![a_n=a_1+\left(n-1\right)d](https://img.qammunity.org/2021/formulas/mathematics/middle-school/e5u60u8wsrdebzmvqawfw4log0ao4iut17.png)
Here,
a₁ = 12a
computing the differences of all the adjacent terms
d = 15a-12a = 3a, d = 18a-15a=3a, d=21a-18a=3a, d=24a-21a=3a
using the nth term formula
![a_n=a_1+\left(n-1\right)d](https://img.qammunity.org/2021/formulas/mathematics/middle-school/e5u60u8wsrdebzmvqawfw4log0ao4iut17.png)
substituting a₁ = 12a, d = 3a
![a_n=12a+\left(n-1\right)3a](https://img.qammunity.org/2021/formulas/mathematics/college/5qsc0dz6mhdbjco8qzautma2scbqy1tncu.png)
![=12a+3na-3a](https://img.qammunity.org/2021/formulas/mathematics/college/ryshjfd09fm394u2npfuby1fc7oh8j232h.png)
![=3na+9a](https://img.qammunity.org/2021/formulas/mathematics/college/gss9ju2cgxqp70jldn1adlsmv2gp94f24d.png)
Therefore, the general rule for the nth term of this sequence will be:
![a_n=3na+9a](https://img.qammunity.org/2021/formulas/mathematics/college/k9n9gy6quugesn4o83d3ws45gsvlp0sltt.png)